2015
DOI: 10.1039/c5ra13004b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and ion-exchange properties of novel hybrid polymer nanocomposites for selective and effective mercury(ii) removal

Abstract: A schematic representation of the current research work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 30 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…In addition, cross-linked poly(dithiocarbamate) and hybrid polymer composite were tested for Hg(II) removal. [29][30][31] Activated carbon bers (ACFs) are lighter and have a larger surface area than activated carbons. Therefore, they are efficient to be used for pollutant removal.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cross-linked poly(dithiocarbamate) and hybrid polymer composite were tested for Hg(II) removal. [29][30][31] Activated carbon bers (ACFs) are lighter and have a larger surface area than activated carbons. Therefore, they are efficient to be used for pollutant removal.…”
Section: Introductionmentioning
confidence: 99%
“…The thermodynamic studies also indicated that the process was spontaneous, feasible, and endothermic. Several other recent and relevant studies reported on mercury adsorption using different adsorbents are discussed …”
Section: Purification Of Mercury‐containing Wastewater Using Low‐costmentioning
confidence: 99%
“…11,12 There has been much research in this eld and many technologies have been developed to remove mercury from water. [13][14][15][16][17][18][19][20][21][22] The techniques include adsorption, ion exchange, chemical precipitation, membrane separation, ltration, chemical oxidation or reduction. Among these techniques, adsorption is regarded as the most promising method due to its easy operation and high efficiency.…”
Section: Introductionmentioning
confidence: 99%